Cyberbullying, uso de redes sociais e sintomas ansiosos e depressivos em adolescentes pernambucanos. - Silva, Davi Ítalo Souza Barbosa da (2023)
With the advent of new Digital Information and Communication Technologies (DICTs), new threats to adolescent mental health emerge, such as cyberbullying - a modern expression of bullying, whose purpose is to attack, expose or humiliate a certain group or individual through digital means. The objective of the current investigation was to analyze part of a database from a multicenter study on social environments and health and well-being behaviors of adolescents, particularly correlating variables on cyberbullying, sociodemographic data, use of social networks, anxious and depressive symptoms. This is a correlational study that analyzes data from 501 teenagers from Recife, of both sexes, aged 13 and 15. The sample was composed of students from the state public school system in the city of Recife-PE, stratified based on the six Political-Administrative Regions (RPAs). To collect data from the multicenter study, three screening instruments were used, all adapted to the Brazilian Portuguese language: 1) Health Behavior in School-aged Children (HBSC) - from which 10 items were selected for the current investigation, four items relating to sociodemographic data, three relating to cyberbullying practices and three to the use of social networks; 2) Spense Children’s Anxiety Scale (SCAS) - from which the 44 items referring to anxiety symptoms were used; 3) Children’s Depression Inventory (CDI) - from which the 27 items related to depression were used. In addition to the descriptive analyses, internal consistency analysis of the SCAS and CDI scales, chi-square, t-test and Spearman correlation were performed. A high internal consistency of the scales was identified using Cronbach's alpha (α = 0.883 and α = 0.912, respectively). The analysis of the sociodemographic profile revealed that the majority were female (62.3%), were 15 years old (61.9%), enrolled in the 1st year of high school (48.8%), self-declared to be of color mixed race (51.3%), spent seven or more hours a day on the internet during the week (33.7%) and lived with their mother (88.4%), father (51.1%) and siblings (54.5%). %). Adolescents in general both self-reported having practiced cyberbullying (43.9%) and having been victims of cyberbullying (32.3%) at least once in the last two months. When comparing the SCAS and CDI scores between the groups of self-declared victims (GVC) and non-victims (GNVC) of cyberbullying, no significant differences were identified regarding anxious symptoms; however, in the CDI there were significantly higher scores in the GVC group (M = 15.4; SD = 9.4) compared to the GNVC (M = 12.8; SD = 9.5) (t = 2.825; gl = 480 ; p < 0.05). The correlation analysis also showed a significant and positive relationship only between the CDI score and the receipt of offensive instant messages (r = 0.125; p < 0.05) and the unauthorized leaking of photos (r = 0.137; p < 0 .01). The SCAS score was significantly and positively correlated with time spent using social networks (r =0.104; p < 0.05). Also, the time spent using social networks was positively correlated with the practice of cyberbullying through offensive messages (r = 0.110; p < 0.05). It is argued that the hypotheses were partially confirmed, mainly with regard to the relationship between cyberbullying practices and depressive symptoms. It is considered that the time of exposure to social networks was also an important variable to be considered in terms of the expression of anxious symptoms and vulnerability to cyberbullying and that further investigations are opportune to support action strategies to reduce digital violence in adolescence.